2013
DOI: 10.1126/scisignal.2003057
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib Potently Induces Endoplasmic Reticulum Stress–Mediated Apoptosis in BRAFV600E Melanoma Cells

Abstract: The V600E mutation in the kinase BRAF is frequently detected in melanomas and results in constitutive activation of BRAF, which then promotes cell proliferation by the mitogen-activated protein kinase (MAPK) signaling pathway. Although the BRAFV600E kinase inhibitor vemurafenib has remarkable antitumor activity in patients with BRAFV600E-mutated melanoma, its effects are limited by the onset of drug resistance. We found that exposure of melanoma cell lines with the BRAFV600E mutation to vemurafenib decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 46 publications
11
104
0
Order By: Relevance
“…A previous report found that the ER stress response that ensues after BRAFi in some BRAF mutant cell lines may contribute to BRAFi-associated apoptosis (48). In our present work, chemical els, as expected, due to simultaneous autophagy induction and distal blockade.…”
Section: Blockade Of Perk-dependent Er Stress Response Limits Brafi-isupporting
confidence: 70%
“…A previous report found that the ER stress response that ensues after BRAFi in some BRAF mutant cell lines may contribute to BRAFi-associated apoptosis (48). In our present work, chemical els, as expected, due to simultaneous autophagy induction and distal blockade.…”
Section: Blockade Of Perk-dependent Er Stress Response Limits Brafi-isupporting
confidence: 70%
“…In BRAF V600E melanoma cells, knockdown of ATF4, an ER stressinduced transcription factor acting in the PERK pathway, markedly reduced vemurafenib-associated cell death. Conversely, vemurafenib combined with either thapsigargin or tunicamycin, both of which are known inducers of ER stress, enhanced apoptosis in vemurafenibresistant or -insensitive melanoma cells (6). These results suggest that pharmacological enhancers of ER stress, particularly those that stimulate the PERK pathway, may be useful adjuncts to vemurafenib treatment and may overcome the rapidly developing drug resistance seen in melanoma patients.…”
Section: Kinase Inhibitors Activate Er Stress and Induce Autophagymentioning
confidence: 67%
“…The ER luminal domains of the three ER stress sensors, PERK, ATF6, and IRE1, are highly homologous, and all three proteins bind GRP78; therefore, it would be expected that the sequestration of GRP78 by BRAF V600E might activate all three ER stress-signaling pathways. On the other hand, earlier studies have shown that GRP78, which is induced by ATF6, is decreased in melanoma cells after vemurafenib exposure (6). At this stage, not only is it unclear how BRAF inhibitors promote BRAF entry into the ER, but it also remains to be determined how and why the sequestration of GRP78 by BRAF preferentially activates PERK.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This mutation modifies the spatial structure of activation P-loop, causing a 500-fold increase in BRAF kinase activity and facilitating the acquisition of secondary genetic events in cancer progression (3). Target therapy for cutaneous melanomas is focused on this mutation: small molecules (vemurafenib and dabrafenib) act as Tyrosine Kinase Inhibitors (TKIs), and interrupt the BRAF/MEK step in RAS/MEK/ERK pathway, inducing apoptosis in mutated cells (4). Less frequent BRAF mutations (5,6) with alterations in the same crucial site, such as Threonine599 and Serine601 (7), have been described.…”
Section: Introductionmentioning
confidence: 99%